Unveiling the Energy Price Tag – Assessing the Degree of Regressivity of Household Energy Expenditures Among European Countries - Ivan Ackermann; Doina Radulescu (CESifo GmbH, 2024)
Policies to address climate change and the energy transition are increasingly gaining ground. However, a large body of research has mainly focused on the efficiency aspect of different instruments rather than their unintended side-effects. Only recently, both policymakers as well as researchers have started to emphasise equity aspects of these policies, since the acceptability of different measures also hinges upon the redistributional implications. This paper contributes to the growing body of research on energy expenditure in-equality in advanced economies by quantifying the regressivity of energy expenditures across 19 European Union countries for the years 2010, 2015, and 2020. We reveal a consistent pattern of regressive energy expenditures across all countries and time periods, with significant variability in the degree and regressivity observed. Our analysis highlights the importance of a nuanced approach to assessing energy expenditure inequality and tailoring suitable energy and climate policies, as countries with the highest or lowest shares of disposable income spent on energy do not necessarily align with those exhibiting the most pronounced regressivity. Tailored policy instruments are essential, particularly when addressing the needs of specific groups, such as low-income households dependent on fossil-based heating systems. However, if broader population segments are affected, more complex solutions may be necessary. We also examine the contributions of various socio-demographic factors to explaining energy expenditures inequality, finding that certain characteristics, such as house-hold size or socio-economic status, contribute to a more even distribution of energy expenditures in the population. These insights suggest that policies aimed at reducing energy expenditure inequality may extend beyond income-based transfers to address the specific needs of different socio-demographic groups.
Keywords: D31; H23; Q48; 330; energy policy; energy expenditures; regressivity